(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Karskanova S. V. From professional self-determination to professional development of future teacher The paper considers the self-determination of young professional and further development of the teacher. Analyzes the components of professional development and professional education. Substantiates the priority of active learning for the development of professional education and psychological training as providing.